Strategic management and regulation of Antarctic tourism - Julia Jabour (2014)
Antarctic tourism is mainly ship-based and managed on a day-to-day basis by the industry using guidelines for behaviour designed specifically for tourist sites. Regulation comes mainly from international shipping law. There are increasing concerns about climate change, shipping accidents and growing tourist numbers, prompting calls for stricter governance to manage growth and risk. The Antarctic Treaty Consultative Parties collaborate with expert organisations to govern tourism but there are still regulatory lacunae that need attention. Initiatives such as a ban on heavier fuel oils in the Antarctic Treaty area and the imposition of a mandatory shipping code will slowly fill that gap. But a new suggestion is offered here to tighten regulation even further: the adoption of sponsoring states for tourism operators from among Antarctic Treaty Consultative Parties. This scheme will introduce a strict element of environmental liability for tourist activities, with greater enforceability.